2022
DOI: 10.1016/j.bjps.2022.01.040
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and cosmetic tourism: A Google trends analysis of public interests and the experience from a tertiary plastic surgery centre

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 3 publications
2
13
0
Order By: Relevance
“…This mirrors the findings of another Google Trends study, which revealed that popularity for plastic surgery topics initially decreased at each lockdown date. 13 Our study also found that search interest began to increase shortly after March 2020 and reached values in 2021 greater than during the prepandemic year (2019) for rest of body procedures. This is similar to the findings of Dhanda et al, 12 stating a noticeable decline in interest in March and April of 2020 relative to the first 2 months of the year with relative interest beginning to increase in May and exceeding interest in January and February.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…This mirrors the findings of another Google Trends study, which revealed that popularity for plastic surgery topics initially decreased at each lockdown date. 13 Our study also found that search interest began to increase shortly after March 2020 and reached values in 2021 greater than during the prepandemic year (2019) for rest of body procedures. This is similar to the findings of Dhanda et al, 12 stating a noticeable decline in interest in March and April of 2020 relative to the first 2 months of the year with relative interest beginning to increase in May and exceeding interest in January and February.…”
Section: Discussionsupporting
confidence: 68%
“…Google Trends is a tool derived from the search engine Google that analyzes the relative interest or popularity of a search term, on a scale from 0 to 100, where 100 represents the greatest popularity for a specific time range. [11][12][13] Using Google search data as a proxy for public interest has been validated in plastic surgery and relates to the number of procedures performed. [13][14][15] The relative search interest was plotted as a function of time for each term.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The internet has facilitated this practice by enabling patients to access information about foreign hospitals, and delivering advertisements for discounted aesthetic surgical procedures [ 4 ]. It is yet to be seen how the COVID-19 pandemic and widespread shutdown of elective procedures in the USA may have influenced interest in cosmetic tourism in the USA, but early analysis from Ireland found increased interest in elective surgery abroad during these shutdowns [ 1 ]. As the number of patients seeking care abroad grows, so does the number of returning patients presenting to US providers with complications.…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients seeking medical care abroad, a practice called “medical tourism,” has grown dramatically in recent decades, to an over $100 billion market-value annually [ 1 3 ]. Historically, the direction of travel for medical care was from less-developed to wealthier nations, but that trend has reversed: patients from wealthy nations with high healthcare costs, including the USA, are now seeking discounted health services in lower-income countries, [ 4 ] and facilities in these destinations have expanded to meet the demand [ 2 ].…”
Section: Introductionmentioning
confidence: 99%